Molecular characterization of the 5S rDNA non-transcribed spacer and reconstruction of phylogenetic relationships in Capsicum - Grabiele, Mauro; Aguilera, Patricia Mabel; Ducasse, Daniel Adrian; Debat, Humberto Julio (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2022)
Capsicum includes ca. 41 species of chili peppers. In this original report we PCR amplified, cloned, sequenced and characterized the 5S rDNA non-transcribed spacer -NTS- in 23 taxa of nine clades of Capsicum, divergent at geographical origin and fruit and chromosome traits, and compared the NTS features throughout Solanaceae. According to GC content, inner variability and regulatory elements, the NTS organizes into three distinct structural regions; genetic variability at the NTS in Capsicum and related genus clusters into defined taxa hierarchies. Based on the reconstruction of a maximum-likelihood phylogenetic tree and phylogenetic networks, NTS sequences of Capsicum and related taxa grouped into well recognized categories -genus, section, clade, species, variety-. An evolutionary scenario arose from combined genetic and phylogenetic NTS data, in which monophyly and lineage diversification over time of Capsicum are addressed. Our analysis is original to include all domesticated species of Capsicum prevailing in germplasm collections and breeding programs, together with a large group of wild taxa that demanded further genetic characterization. The NTS set up as a double purpose marker in Capsicum, to directly evaluate genetic variability and reconstruct phylogenetic relationships to a broad extent, and constitutes a valuable tool for germplasm characterization and evolutionary studies within Solanaceae.